1.The equivalent of (a+√b)(a-√b)=__________ *

Question

1.The equivalent of (a+√b)(a-√b)=__________ *

in progress 0
Ximena 1 month 2021-08-16T20:19:22+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-08-16T20:20:48+00:00

    Step-by-step explanation:

    The answer is:

    using  \:  {a}^{2}  -  {b}^{2}  =    { (a + b) } { (a - b)}

    (a)² – (√b²) = a² – b

    Hope this helps you….

    0
    2021-08-16T20:21:17+00:00

    Answer:

    The answer of (a+√b)(a-√b) =

    ( {a}^{2}  - ( \sqrt{b} ) {}^{2} )

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )